2022
DOI: 10.3390/rs14153799
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plasma Sheath’s Velocity Field on ISAR Imaging of Hypersonic Target

Abstract: Plasma sheath poses a serious challenge to inverse synthetic aperture radar (ISAR) imaging of hypersonic targets. This paper investigated the distribution characteristics of the electron density and velocity field in the plasma sheath surrounding the hypersonic target in various flight scenes. The incident depth and reflective surface of electromagnetic (EM) waves with X-band, Ku-band, and Ka-band can be determined based on the plasma frequency. We established the echo model coupled with the velocity field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Interestingly, inverse synthetic aperture radar remains effective in the X band (8-12 GHz, see Xie et al, 2022).…”
Section: Radar-based Sensingmentioning
confidence: 99%
“…Interestingly, inverse synthetic aperture radar remains effective in the X band (8-12 GHz, see Xie et al, 2022).…”
Section: Radar-based Sensingmentioning
confidence: 99%
“…In [23,24], a time-varying plasma sheath model based on the Scattering Matrix Method (SMM) was established, where the amplitude attenuation and phase shift of the radar echo signal were examined. In addition, by integrating the velocity field distribution of the non-uniform plasma sheath, a plasma sheath inhomogeneous reflection model is constructed in [3,[25][26][27][28]. It has been shown that the radar echo suffers from multitarget phenomenon on the 1-D range profile.…”
Section: Introductionmentioning
confidence: 99%